Targeted drug delivery in covalent organic nanosheets (CONs) via sequential postsynthetic modification - Mitra, Shouvik; Sasmal, Himadri Sekhar; Kundu, Tanay; Kandambeth, Sharath; Math, Kavya; Diaz Diaz, David; Banerjee, Rahul (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as a new class of functional two-dimensional (2D) porous organic polymeric materials with a high accessible surface, diverse functionality, and chemical stability. They could become versatile candidates for targeted drug delivery. Despite their many advantages, there are limitations to their use for target specific drug delivery. We anticipated that these drawbacks could be overturned by judicious postsynthetic modification steps to use CONs for targeted drug delivery. The postsynthetic modification would not only produce the desired functionality, it would also help to exfoliate to CONs as well. In order to meet this requirement, we have developed a facile, salt-mediated synthesis of covalent organic frameworks (COFs) in the presence of p-toluenesulfonic acid (PTSA). The COFs were subjected to sequential postsynthetic modifications to yield functionalized targeted CONs for targeted delivery of 5-fluorouracil to breast cancer cells. This postsynthetic modification resulted in simultaneous chemical delamination and functionalization to targeted CONs. Targeted CONs showed sustained release of the drug to the cancer cells through receptor mediated endocytosis, which led to cancer cell death via apoptosis. Considering the easy and facile COF synthesis, functionality based postsynthetic modifications, and chemical delamination to CONs for potential advantageous targeted drug delivery, this process can have a significant impact in biomedical applications.